Long‐term outcomes in patients with restrictive filling following ST‐segment elevation myocardial infarction. Issue 3 (March 2014) - Hee, L.; Brennan, X.; Chen, J.; Allman, C.; Whalley, G. A.; French, J. K.; Juergens, C. P.; Thomas, L.
Abstract This study evaluated the effect of restrictive filling pattern (RFP) on 5‐year outcomes in patients following ST‐segment elevation myocardial infarction (STEMI). A hundred STEMI patients treated either by rescue or primary percutaneous coronary intervention with an echocardiogram performed within 6 weeks of STEMI comprised the study group. Creatinine kinase (CK) and left ventricular ejection fraction were independent determinants of RFP, and RFP was an independent predictor of cardiac and all‐cause mortality at median follow up of 5 years.